2018
DOI: 10.1111/jocd.12503
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in acne vulgaris patients treated with oral isotretinoin

Abstract: This study concluded that vitamin D may play a potential role in pathogenesis of acne vulgaris or acne vulgaris may have a negative effect on vitamin D synthesis. Further studies are needed to confirm these potential relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
4
37
0
1
Order By: Relevance
“…In this study, patients showed significantly lower serum 25(OH)D 3 concentration when compared to controls, suggesting that VitD deficiency may be a risk factor for the development of AV. In agreement, previous studied stated that VitD deficiency causes increase sebum production, follicular hyperkeratinization, P acnes overgrowth and exacerbates inflammation in AV . P acnes , via toll‐like receptors, are responsible for CD4 + lymphocytes and macrophages activation which aggravates the pilosebaceous vasculature, pronounces ductal hyperproliferation, and in turn promotes more microbial proliferation .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, patients showed significantly lower serum 25(OH)D 3 concentration when compared to controls, suggesting that VitD deficiency may be a risk factor for the development of AV. In agreement, previous studied stated that VitD deficiency causes increase sebum production, follicular hyperkeratinization, P acnes overgrowth and exacerbates inflammation in AV . P acnes , via toll‐like receptors, are responsible for CD4 + lymphocytes and macrophages activation which aggravates the pilosebaceous vasculature, pronounces ductal hyperproliferation, and in turn promotes more microbial proliferation .…”
Section: Discussionsupporting
confidence: 90%
“…In agreement, previous studied stated that VitD deficiency causes increase sebum production, follicular hyperkeratinization, P acnes overgrowth and exacerbates inflammation in AV. 1,9,10 P acnes, via toll-like receptors, are responsible for CD4 + lymphocytes and macrophages activation which aggravates the pilosebaceous vasculature, pronounces ductal hyperproliferation, and in turn promotes more microbial proliferation. 10,11 VitD increases forkhead box 1 (FOXO1) transcription and downregulates mTORC1, which is thought to be a main regulator of cell growth and lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it is found that vitamin D deficiency is associated with many chronic diseases including cancers, cardiovascular diseases, metabolic syndrome, infectious and autoimmune skin diseases, also, AV 19,21,22 . It is considered that vitamin D is important not only in calcium homeostasis, but also in immune system regulation, cell growth and differentiation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is also known as anticomedogenic and antioxidant. The deficiency of vitamin D may facilitate the pathogenesis of AV 6,19 . The relationship between vitamin D and AV depends on possible anti-inflammatory effects of vitamin D 24 .…”
Section: Discussionmentioning
confidence: 99%